(untitled) (Andamios, Revista de Investigación Social, 2007)
The main thesis of the article consists of showing, confronted with rationalist positions (such as Porfirio Miranda’s, Karl-Otto Apel’s or Mario Rojas’), that it is necessary to establish the scope of discourse from a wider horizon. Rationalism tends to define human being essentially as a thinking, rational being. It is necessary to show that human being is, above all, a “living carnality”. Life is human being’s reality mode; affectivity and rationality are two dimensions of the living being itself, i. e., of life. Life is not a condition of reason or argument. These two are not the essential moment of human being and its finality, but, on the contrary, life is the fundamental moment and rationality a dimension to achieve a full life. The foundation of ethics has to derive from the reality of the living being and can also use a transcendental foundation of rationality bearing always in mind that it is not the last instance from a metaphysical point of view and not purely discoursive.